Upstream law and regulation : a global guide - Pereira, Eduardo, editor; Talus, Kim, editor (London : Globe Law and Business)
This practical new handbook analyses the most relevant petroleum provinces. The book summarises the upstream regulation and the key concerns in over 30 important and emerging oil and gas jurisdictions. Issues featured include the key terms of the petroleum law, the types of legal arrangement in place (ie, concession agreement, production sharing contract or service agreement), the fiscal terms, how to qualify to acquire acreage, type of governing law, dispute resolution mechanisms and governmental control.